STRATEGI ADAPTASI MAHASISWA PERANTAUAN ASAL JAKARTA DI FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS SAM RATULANGI MANADO - Caroline Monic Debora; Maria Heny Pratiknjo; Nasrun Sandiah (HOLISTIK, Journal of Social and Culture, 2021)
Merantau for the sake of education is also considered, as an effort to prove the quality of self as an independent adult and responsible in making decisions. And to actively adjust to the new environment, an overseas student from Jakarta uses various actions to adapt. Adaptation is a key concept in looking at human relationships with the environment. Culture shock is a picture of the profound and negative responses of depression, frustration and disorientation experienced by individuals living in one new environment. The purpose of this research is to find out the adaptation strategy of overseas students from Jakarta at the Faculty of Social and Political Sciences, Sam Ratulangi University Manado. This research uses qualitative descriptive method, because qualitative method as research procedure that produces descriptive data in the form of written or oral words directly. Informants in this study there are 7 overseas students from Jakarta at the Faculty of Social and Political Sciences, Sam Ratulangi University, Manado. Data collection techniques used are data collection techniques used, namely observation, interview, and documentation. And data analysis techniques include data reduction, data display, conclusion and verifikas. The results showed that overseas students from Jakarta can adapt by adjusting to such as living independently, by living away from parents or family, by learning new things such as washing dishes and washing their own clothes. Learn to use Manado language in the learning and teaching process, and follow several campus organizations to be able to mingle and get along with other students. Obstacles – obstacles in adapting are faced by having an open attitude and accepting all the differences that exist. Keywords : Adaptation, Overseas, Students